Microbiota and Tuberculosis: A Potential Role of Probiotics, and Postbiotics - Liu, Yue; Wang, Jiaqi; Wu, Changxin (Frontiers in Nutrition, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis attacking the lungs and other organs, is one of the most common infectious disease worldwide. According to WHO 2020 report, a quarter of the world’s population were infected with M. tuberculosis, and approximately 1.4 million people died of TB. Therefore, TB is a significant public health concern, which requires cost-effective strategies. The microbiota has been considered as a “forgotten organ” and a complex dynamic ecosystem, which plays a significant role in many physiological processes, and its dysbiosis is closely associated with infectious disease. Recently, a few studies have indicated associations between TB and microbiota. This review summarises studies concerning the alterations of gut, and respiratory microbiota in TB, and their relationship with host suspensibility to M. tuberculosis infection, indicating that microbiota signatures in different stage in TB progression could be considered as biomarkers for TB diagnosis and control. In addition, the potential role of probiotics, and postbiotics in TB treatment was discussed.